Preventive Measures for Forest Biomass Extraction Beyond Increment in the Western Ghats, India - Hegde, Seema S. (Indian Forester, 2015)
The study was carried out in four selected villages of Uttara Kannada district in the Western Ghats with an aim to present the annual change in biomass using estimated stock and extraction, and to estimate the reduced extraction due to conservation practices. The data collected from a vegetation survey of eight one hectare sites in the forests, and a biomass extraction survey involving 247 households were subjected to a sensitivity analysis of community’s pressure on the forests using the estimates of mean annual increment (MAI) in biomass quoted by various studies. The results show that at an MAI rate of 2.1 t/ha, on an average, the annual extraction by the community is 62% of the increment in biomass, however the values range from 143% to 39% between the villages. A shift to fuel efficient stoves and live fences by a little more than a quarter of the surveyed households shows a reduction in annual biomass extraction to 56% of its MAI, and a potential reduction to 17% in case all the households adopt conservation practices.